2017
DOI: 10.1017/qua.2016.15
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary paleoenvironmental analysis of permafrost deposits at Batagaika megaslump, Yana Uplands, northeast Siberia

Abstract: A megaslump at Batagaika, in northern Yakutia, exposes a remarkable stratigraphic sequence of permafrost deposits 50-80 m thick. To determine their potential for answering key questions about Quaternary environmental and climatic change in northeast Siberia, we carried out a reconnaissance study of their cryostratigraphy and paleoecology, supported by four rangefinder 14 C ages. The sequence includes two ice complexes separated by a unit of fine sand containing narrow syngenetic ice wedges and multiple paleoso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
73
0
6

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 73 publications
(83 citation statements)
references
References 38 publications
4
73
0
6
Order By: Relevance
“…Our more comprehensive assessment of RTS dynamics provides new information on the inter-slump and inter-annual variability in the Eureka Sound Lowlands study region. Our observations are comparable to observations from the low Arctic that also found an increase in the occurrence of RTSs over the last several decades (Lantz and Kokelj 2008, Günther et al 2015, Segal et al 2016, Kokelj et al 2017, Murton et al 2017, Lewkowicz and Way 2019. Comparing average retreat rates from our study to studies in the low Arctic shows this area has generally less overall mean annual headwall retreat (table 3).…”
Section: Rts Occurrence and Retreat Ratessupporting
confidence: 90%
See 1 more Smart Citation
“…Our more comprehensive assessment of RTS dynamics provides new information on the inter-slump and inter-annual variability in the Eureka Sound Lowlands study region. Our observations are comparable to observations from the low Arctic that also found an increase in the occurrence of RTSs over the last several decades (Lantz and Kokelj 2008, Günther et al 2015, Segal et al 2016, Kokelj et al 2017, Murton et al 2017, Lewkowicz and Way 2019. Comparing average retreat rates from our study to studies in the low Arctic shows this area has generally less overall mean annual headwall retreat (table 3).…”
Section: Rts Occurrence and Retreat Ratessupporting
confidence: 90%
“…Reported retreat rates of RTSs in northwestern Canada range between 7.2 and 26.7 m yr −1 (De Krom and Pollard 1989, Lantuit and Pollard 2008. The appearance of 'megaslumps' has recently appeared in scientific literature for RTS areas greater than 20 ha (Günther et al 2015, 2017, Murton et al 2017. Widespread RTS development has been observed in recent decades (Lantz and Kokelj 2008, Segal et al 2016, Khomutov et al 2017, Kokelj et al 2017 and has been observed to induce a change in vegetation communities (Lantz et al 2009, Thienpont et al 2013, Cray and Pollard 2015, and release sediments and solutes that impact terrestrial and aquatic ecosystems (Kokelj and Lewkowicz 1999, Mesquita et al 2010.…”
Section: Introductionmentioning
confidence: 99%
“…Mean d values at the coastal sites are higher (compared to MIS 3), between 4 ‰ and 12 ‰ (e.g. Opel et al, 2011;Meyer et al, 2002b;Wetterich et al, 2008. In contrast, in the Yana Highlands, the Late Holocene mean d value of 6 ‰ is lower compared to MIS 3, whereas Late Holocene d values in central Yakutia (between 6 ‰ and 11 ‰) are rather similar to MIS 3 values (Popp et al, 2006).…”
Section: Holocenementioning
confidence: 90%
“…One of the most conspicuous manifestations of thermokarst is the retrogressive thaw slump (RTS; Fig. 1), which develops as a result of mass wasting in ice-rich glacial deposits across northwestern Canada, Alaska, and western Siberia (Kokelj et al, 2017a) and in Yedoma regions of Alaska and Siberia (Murton et al, 2017). Thaw slumps are widespread throughout glaciated terrain in the western Canadian Arctic (Kokelj et al, 2017a;, including on the Peel Plateau .…”
Section: Introductionmentioning
confidence: 99%